Caste Conflicts on Campuses: Examining Diversity Research to Transform Indian Universities into Inclusive Learning Spaces. Issue 2 (December 2019) - Rathod, Bharat
Abstract: The presence of a significant and growing population of lower caste students on college campuses has been perceived as a challenge to the historical hegemony of higher castes. Therefore, in the last decade alone, numerous incidents of caste-based discrimination and suicides of Dalit students have been reported on the campuses across the country. However, there is scarcely any research on the changed demographic in higher education and its implications on students and the campus climate. The student diversity without institutional policy to benefiting from the diversity, higher education institutions are facing social justice, discrimination and diversity issues. The article explores diversity research from the United States (US) higher education contexts to develop a theoretical understanding and discusses the significance of campus climate frameworks to assess students' perceptions and experiences about their campuses. The campus climate scholarship suggests that institutional commitment to diversity fosters learning outcomes of all students and facilitates critical institutional support to marginalized students. Further, a systematic understanding of the campus climate that can lead to an institutional policy reform to foster a more inclusive and democratic ethos in Indian universities.